Sex differences in coronary artery calcium progression: The Korea Initiatives on Coronary Artery Calcification (KOICA) registry. - Wonjae Lee; Yeonyee E Yoon; Sang-Young Cho; In-Chang Hwang; Sun-Hwa Kim; Heesun Lee; Hyo Eun Park; Eun Ju Chun; Hyung-Kwan Kim; Su-Yeon Choi; Sung Hak Park; Hae-Won Han; et al. (PLoS ONE)
Even with increasing awareness of sex-related differences in atherosclerotic cardiovascular disease (ASCVD), it remains unclear whether the progression of coronary atherosclerosis differs between women and men. We sought to compare coronary artery calcium (CAC) progression between women and men. From a retrospective, multicentre registry of consecutive asymptomatic individuals who underwent CAC scoring, we identified 9,675 men and 1,709 women with follow-up CAC scoring. At baseline, men were more likely to have a CAC score >0 than were women (47.8% vs. 28.6%). The probability of CAC progression at 5 years, defined as [√CAC score (follow-up)-√CAC score (baseline)] ≥2.5, was 47.4% in men and 29.7% in women (p<0.001). When we stratified subjects according to the 10-year ASCVD risk (<5%, ≥5% and <7.5%, and ≥7.5%), a sex difference was observed in the low risk group (CAC progression at 5 years, 37.6% versus 17.9%; p<0.001). However, it became weaker as the 10-year ASCVD risk increased (64.2% versus 46.2%; p<0.001, and 74.8% versus 68.7%; p = 0.090). Multivariable analysis demonstrated that male sex was independently associated with CAC progression rate among the entire group (p<0.001). Subgroup analyses showed an independent association between male sex and CAC progression rate only in the low-risk group. The CAC progression rate is higher in men than in women. However, the difference between women and men diminishes as the 10-year ASCVD risk increases.